The Centrally Sponsored Programme for the Improvement of Secondary Education Strengthening of Science Laboratories and Special Training of Science Teachers. (Crash Programme) - Planning Commission (Planning Commission, 1967)
At a meeting held in Yojana Bhavan, New Delhi, on the. 14th December, 1966, under the chairmanship of the Secretary, Planning Commission, and attended by representatives of Union Ministries of Education and Finance and the University Grants Commission, it was decided to. request, the Programme Evaluation Organisation of the Planning. Commission to make a quick evaluation of the progress of the centrally sponsored schemes relating to the strengthening of science teaching, in schools (Crash Programme). Since the Programme Evaluation Organisation was unable to take up this assignment owing to its preoccupation with other enquiries, it was decided to entrust the job to an Evaluation Team consisting of Shri A.H. Hemrajani, Director (Education), Planning Commission and Dr. M. C. Pant, Professor of Science Education in the Department of Science Education, National Council of Educational Research and Training.
An Evaluation Report by Shri A. H. Hemrajani Director (Education), Planning Commission and Dr. M. C. Pant Professor of Science Education, Department of Science Education, National Council of Educational Research and Training